1999
DOI: 10.1073/pnas.96.20.11519
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human neurotropic JC virus DNA sequence and expression of the viral oncogenic protein in pediatric medulloblastomas

Abstract: Medulloblastoma represents greater than 25% of childhood intracranial neoplasms and is considered a highly malignant tumor. This tumor, which arises predominantly in the cerebellar vermis, preferentially affects children between the ages of 5 and 15. Although the etiology of medulloblastomas in humans remains unknown, results from several experiments have indicated that the human neurotropic JC virus (JCV) is able to induce cerebellar neoplasms in rodents that exhibit a phenotype similar to that of human medul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 39 publications
(38 reference statements)
7
107
3
Order By: Relevance
“…In contrast, quiescent mouse Bs-1b, Bs-1c, BsB8 cells (Figure 2b,d,f) and human D283 Med cells (Figure 2j), tested with the antipY1316 antibody showed much weaker di use staining, similar to the background staining obtained when the primary antibody was omitted from the reaction (Figure 2i picture B). These results indicate that anti- (Krynska et al, 1999).…”
Section: Detection Of Activated Igf-ir In Medulloblastoma Cell Linessupporting
confidence: 53%
“…In contrast, quiescent mouse Bs-1b, Bs-1c, BsB8 cells (Figure 2b,d,f) and human D283 Med cells (Figure 2j), tested with the antipY1316 antibody showed much weaker di use staining, similar to the background staining obtained when the primary antibody was omitted from the reaction (Figure 2i picture B). These results indicate that anti- (Krynska et al, 1999).…”
Section: Detection Of Activated Igf-ir In Medulloblastoma Cell Linessupporting
confidence: 53%
“…Polyomavirus Tag has several biochemical and biological properties: ATPase, helicase, clastogenic and mutagenic activities; it induces cellular and viral DNA replication and it binds tumour suppressor gene products such as p53 and pRb [9]. Although no direct roles for JCV in the onset or progression of human brain tumours were assessed, recent studies found JCV DNA associated with brain neoplasms in the absence of PML [12,48,49]. SV40 sequences have been detected in human brain tumours of different histological types and other human neoplasms by several investigators [9].…”
Section: Discussionmentioning
confidence: 99%
“…Human JCV is the causative agent of PML [11], and JCV DNA sequences and its large T antigen (Tag) oncoprotein have been detected in human medulloblastomas [12]. BKV is associated with diseases of immunocompromised patients, and has been detected in the brain and cerebrospinalĀÆuid (CSF) of an AIDS patient with meningo-encephalitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Barbara Krynska (MCP Hannemann University, Philadelphia, USA) reported that JC virus was present in 11/23 medulloblastomas tested (Krynska et al, 1999) and 5/11 JC containing medulloblastomas also contained SV40 sequences. Production of the JC virus tumor antigen was detected in the nuclei of four of these tumors.…”
Section: Sv40 and Human Brain Tumorsmentioning
confidence: 99%